2004
DOI: 10.1539/joh.46.448
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Status, Shift Work, and Occupational Accidents among Hospital Nurses in Japan

Abstract: Mental Health Status, Shift Work, and Occupational Accidents among Hospital Nurses in Japan: Kenshu Suzuki, et al. Department of Public Health, School of Medicine, Nihon University—A questionnaire survey was conducted with questions from the 12‐item General Health Questionnaire, among others, targeting 4,407 nurses in 8 general hospitals in Japan, in the hope of improving the work environment of nurses and to provide data that will allow a discussion of the measures necessary for preventing medical errors, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
134
2
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(152 citation statements)
references
References 19 publications
6
134
2
10
Order By: Relevance
“…Indeed, depressive symptoms and shift work schedules are major factors that increase the risk that hospital workers will experience accidents during their job tenure (Guastello et al 1999). In addition, a study that used GHQ-12 to examine the correlation between nurses' mental health level and their rate of occupational accidents reported that those in a poor state of mental health showed a high OR of experiencing occupational accidents (e.g., medication accidents, mistaken operation of medical machines, and injuries by needles; Suzuki et al 2004). Moreover, a recent pilot study reported that female workers who had experienced occupational injuries complained of depressive symptoms more than those who had not experienced injuries (Peele and Tollerud 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, depressive symptoms and shift work schedules are major factors that increase the risk that hospital workers will experience accidents during their job tenure (Guastello et al 1999). In addition, a study that used GHQ-12 to examine the correlation between nurses' mental health level and their rate of occupational accidents reported that those in a poor state of mental health showed a high OR of experiencing occupational accidents (e.g., medication accidents, mistaken operation of medical machines, and injuries by needles; Suzuki et al 2004). Moreover, a recent pilot study reported that female workers who had experienced occupational injuries complained of depressive symptoms more than those who had not experienced injuries (Peele and Tollerud 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Because it has various physiological influences on the immune, blood circulatory, and central nervous systems, cortisol is an important hormone to consider when determining physical and mental health 22,23) . Since salivary cortisol is highly correlated with blood cortisol level, and saliva can be sampled less invasively than blood, it is often used in studies on circadian rhythm and work-related stress 24−32) .…”
Section: Salivary Cortisolmentioning
confidence: 99%
“…Night-shift nurses who work against the circadian rhythm are prone to fatigue and decreased work performance, resulting in occurrences of medi-cal accidents and errors at night 13−20) . Moreover, some studies have reported that errors and medical incidents during work by nurses with depression tend to happen particularly in the early morning 21,22) . Although it has been noted in a large number of studies that shift-working nurses are subject to depression, and that medical errors and incidents are caused by them more frequently in the early morning when they are on a night shift, the factors associated with these tendencies have not been objectively examined.…”
mentioning
confidence: 99%
“…Night-shift nurses who work against the circadian rhythm are susceptible to fatigue and decreased work performance, resulting in the occurrence of medical accidents and errors at night (Grossman, 1997 andOriyama et al, 2011). Moreover, some studies have reported that night-shift nurses are prone to depression causing errors and medical incidents during work which happen particularly in the early morning (Gold et al, 1992 andSuzuki et al, 2004).…”
Section: Introductionmentioning
confidence: 99%